Benchmarking Financial Systems around the World - Čihák, Martin; Demirgüç-Kunt, Aslı; Feyen, Erik; Levine, Ross (World Bank, Washington, DC, 2013)
This paper introduces the Global Financial Development Database, an extensive dataset of financial system characteristics for 205 economies from 1960 to 2010. The database includes measures of (a) size of financial institutions and markets (financial depth), (b) degree to which individuals can and do use financial services (access), (c) efficiency of financial intermediaries and markets in intermediating resources and facilitating financial transactions (efficiency), and (d) stability of financial institutions and markets (stability). The authors document cross-country differences and time series trends.